2023
DOI: 10.1039/d2en00545j
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanomaterial-based membranes for water and wastewater treatment under electrochemical assistance

Abstract: Membrane separation has been widely used in water and wastewater treatment due to its relatively low cost, easy operation and high efficiency. However, the current membranes suffer from the trade-off...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 305 publications
0
5
0
Order By: Relevance
“…Regarding their chemical composition, waste carbon nanofibers typically comprise a carbon fiber substrate intermingled with an array of specific functional elements, such as nitrogen, sulfur, phosphorus (NSP), and metallic elements. [33][34][35] To meet the mechanical strength criteria set by various practical applications, these nanofibers are often integrated with matrix composites-namely resins, metals, and ceramics-to form carbon fiber reinforced polymers (CFRPs). 36,37 Notably, carbon nanofiber-reinforced epoxy resin composites boast unparalleled specific strength and modulus among existing structural materials, thus finding extensive applications in the aerospace and automotive industries.…”
Section: Conventional Recycling Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding their chemical composition, waste carbon nanofibers typically comprise a carbon fiber substrate intermingled with an array of specific functional elements, such as nitrogen, sulfur, phosphorus (NSP), and metallic elements. [33][34][35] To meet the mechanical strength criteria set by various practical applications, these nanofibers are often integrated with matrix composites-namely resins, metals, and ceramics-to form carbon fiber reinforced polymers (CFRPs). 36,37 Notably, carbon nanofiber-reinforced epoxy resin composites boast unparalleled specific strength and modulus among existing structural materials, thus finding extensive applications in the aerospace and automotive industries.…”
Section: Conventional Recycling Technologiesmentioning
confidence: 99%
“…26,27 Addressing these challenges, scientific categorization, effective recycling, and reuse of discarded nanocarbon fibers are crucial, offering both environmental and economic benefits. Previously, there have been comprehensive reviews that adequately summarize actual application cases of carbon nanofibers in various fields 24,34 and the current recycling status of regular composite carbon fibers. 28,29 Unfortunately, after being subjected to standard recycling processes, nanofiber waste loses its specific nanostructure, relegating it to cheap filler usage and significantly diminishing its economic value.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental observations have also shown that aligned CNT membranes, with their pore channels constructed by the inner walls, allow for ultrafast but selective mass transport, which is facilitated by the atomically smooth graphitic inner surface. On the other hand, nonwoven CNT membranes constructed by randomly stacking CNTs possess high porosity and high permeance, making them useful as a platform for other functional membranes, such as antibacterial and photocatalysis membranes [ 47 49 ]. CNTs exhibit a high aspect ratio, exceptional mechanical strength, low density, and high stiffness.…”
Section: Nanostructured Materials For Membrane Developmentmentioning
confidence: 99%
“…The ion fluxes due to diffusion and electro-migration are proportional to this factor according to Equation (3). At the same time, the membrane permeability A and, consequently, the solvent flux J V are usually proportional to this factor; see ( 9) and (10). Thus, it follows from ( 3) and ( 4) that the variation of ε does not affect salt rejection.…”
Section: The Influence Of Other Factorsmentioning
confidence: 99%